Integrating Indigenous Knowledge in Science Education: A Systematic Review of Strategies, Models, and Impacts - Rasmawan, Rahmat; Haryani, Sri; Susilaningsih, Endang; Handayani, Langlang (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Integrating Indigenous knowledge (IK) has received significant attention in the context of achieving science learning that is relevant, contextual, and connected to students' daily lives. This study aims to systematically review empirical research that documents the integration of IK programs in science learning. From 227 literature sources, 43 were selected for analysis. The findings indicate that developmental research predominates the methodology employed, with experimental and qualitative descriptive research following. The implementation of integrated-science learning programs falls into several categories, including project-based learning, discussions, technological applications, field research, local knowledge integration, cultural practices, and reflective exercises. The positive outcomes of this process encompass enhanced appreciation of nature and biodiversity, cultural awareness, improved thinking skills, better subject content mastery, increased motivation, higher learning engagement, a more comprehensive understanding of the nature of science (NOS), and greater appreciation of scientific principles. Key recommendations include fostering collaboration with Indigenous communities, creating comprehensive learning modules, and providing continuous professional development for teachers.